Determinants of Secondary Adjustment Tax Disputes in Transfer Pricing: An Empirical Study in the Indonesian Context - Auliya, Hubaya Arif; Rosid, Arifin (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p06, 2024)
Tax disputes involving secondary adjustments in transfer pricing at the Indonesian Tax Court have risen, despite a decline in cases filed by the Directorate General of Taxes between 2021 and 2023. This study examines the underlying causes of these disputes through Root Cause Analysis (RCA) and Fishbone Diagrams. The analysis draws on 358 court rulings, a comprehensive literature review, and semi-structured interviews with eight key stakeholders, including judges, tax auditors, tax objection officers, and tax consultants. The findings highlight several critical factors contributing to these disputes. These include the lack of a clear definition for disguised dividends—an issue arising from the application of secondary adjustments under Indonesian regulations—varying interpretations of Ministry of Finance Regulation No. 22/2020, limited technical competence among tax auditors, and aggressive tax audit targets. These factors create legal uncertainty and increase the likelihood of disputes. To address these challenges, the study recommends clarifying relevant regulations, strengthening tax auditor training programs, and shifting the focus of tax audits from quantity to quality. Implementing these measures is expected to enhance legal certainty, reduce the frequency of disputes, and contribute to a more robust and effective tax administration system in Indonesia. Keywords: Secondary Adjustment; Transfer Pricing; Tax Disputes; Indonesian Tax Court; Root Cause Analysis